The importance of disturbance and forest structure to bird abundance in the Black Hills. (16th March 2019) - Matseur, Elizabeth A; Millspaugh, Joshua J; Thompson, Frank R; Dickerson, Brian E; Rumble, Mark A
Abstract: Many North American birds associated with forest disturbances such as wildfire and mountain pine beetle ( Dendroctonus ponderosae ) outbreaks are declining in abundance. More information on relationships between avian abundance and forest structure and disturbance is needed to guide conservation and management. Our objective was to determine densities of American Three-toed Woodpecker ( Picoides dorsalis ), Black-backed Woodpecker ( Picoides arcticus ), Red-breasted Nuthatch ( Sitta canadensis ), Brown Creeper ( Certhia americana ), and White-winged Junco ( Junco hyemalis aikeni ) in relation to vegetation characteristics and disturbance at the point and landscape level in the Black Hills and Bear Lodge Mountains of South Dakota and Wyoming. We conducted 3 point counts from late March to late June 2015 and 2016 at more than 2, 300 locations distributed across a gradient of forest structure and disturbance types. We estimated densities using 3-level hierarchical time-removal models that simultaneously estimated abundance, availability, and detection probability. Black-backed Woodpeckers were positively related to percent area in 1- to 3-year-old wildfires and Brown Creepers were positively associated with percent area in 4- to 5-year-old wildfires; however, Red-breasted Nuthatches were negatively related to percent area in 3- to 5-year-old wildfires. With the exception of American Three-toed Woodpeckers, species were positively related to percent cover of beetle-killed trees. Brown Creepers, White-winged Juncos, and Red-breasted Nuthatches had mixed responses to percent overstory canopy cover. White-winged Juncos also had a positive association with percent ground vegetation at the point and landscape level. Brown Creepers were strongly linked with spruce vegetation type. American Three-toed Woodpeckers, which are thought to occupy spruce forest in the Black Hills, did not show a strong relationship with any covariates. Maintaining some areas of natural disturbances along with heterogeneity of vegetation characteristics within stands and at the landscape scale will benefit the needs of a diverse bird community in the Black Hills.